Efek Perubahan Lingkungan terhadap Output Pertanian Indonesia - Prastanika, Winar Wahyu; Putri, Amanda Chairunisa Gheana; Samaya, Najwa Fairus; Hutajulu, Ronald; Aliy, Tiara Rahma; Budiasih, Budiasih (Politeknik Statistika STIS, 2023)
This study aims to explain the influence of the environment on Indonesia's agricultural output in 1990-2021 in the long and short term. The type of data used is secondary data which is time series data with annual units obtained from the World Bank. The analytical method used is ECM (Error Correction Model) with the help of Eviews-10 software. The results of the study show that in the long term CO2 growth has a significant negative effect, but in the short term it has a significant positive effect on agricultural output growth. In addition, the growth in the use of chemical fertilizers has a negative effect on agricultural output in the long and short term. In the long run, the growth in the area of cereal production land and the growth in the number of rural populations have a positive effect. In the short term, the growth in the area of cereal production has a positive effect, while the growth in the number of rural population has a positive effect. Partially, there are also growth variables, increasing rainfall and increasing air temperature which have no significant effect on the growth of agricultural output in the long and short term.